THE LEXEME DOKTOR IN THE DIALECTS OF THE CZECH LANGUAGE - Kopecká, Tereza (Bohemica Olomucensia, 2021)
The article deals with the lexeme doktor in the dialects of the Czech language. In contrast to its use in literary language, the word has been analyzed in terms of phonetic variability, semantics and word formation.
Keywords: dialectology; lexicology; word formation; Czech language; lexeme doktor